ANALISIS PENERAPAN PSAK NOMOR 46 PAJAK PENGHASILAN ATAS LAPORAN KEUANGAN TAHUN 2021 DI CV. NUSANTARA MAKMUR SEJAHTERA - Leslie, Jennifer; Tri Setyo Mulyani, Hendarti; Novika (STIE IBEK Pangkalpinang, 2022)
Companies often face obstacles in the process of recognizing all the consequences of tax calculations on financial statements. This causes differences between commercially recognized financial statements and fiscal financial statements. CV. Nusantara Makmur Sejahtera is a company that sells various types of facial, hair and body beauty products. The purpose of this study was to evaluate whether CV. Nusantara Makmur Sejahtera has implemented PSAK No. 46 in the company's financial statements. The research uses qualitative methods with descriptive analysis, namely looking at the 2021 financial reports. The data used in this study is primary data, and the type of data used is documentary data. The research finding is that there is a difference between the financial statements that are recognized fiscally and commercially. This causes a negative fiscal correction to the depreciation account. Based on the calculation, the total negative fiscal correction is Rp. 58,830,650. So that the application of PSAK No. 46 in the financial statements of CV. Nusantara Makmur Sejahtera is not perfect yet. To overcome this problem, the company must follow the tax regulations that have been set by PSAK No. 46